General Anesthetic Versus Light Sedation: Effect on Pediatric Endoscopy Wait Times - Christine Edwards; Vikram Kapoor; Christopher Samuel; Robert Issenman; Herbert Brill (Canadian Journal of Gastroenterology)
BACKGROUND: Wait times are an important measure of health care system effectiveness. There are no studies describing wait times in pediatric gastroenterology for either outpatient visits or endoscopy. Pediatric endoscopy is performed under light sedation or general anesthesia. The latter is hypothesized to be associated with a longer wait time due to practical limits on access to anesthesia in the Canadian health care system.